Overcoming obstacles to repurposing for neurodegenerative disease. (24th June 2014) - Shineman, Diana W.; Alam, John; Anderson, Margaret; Black, Sandra E.; Carman, Aaron J.; Cummings, Jeffrey L.; Dacks, Penny A.; Dudley, Joel T.; Frail, Donald E.; Green, Allan; Lane, Rachel F.; Lappin, Debra; et al.
Abstract Repurposing Food and Drug Administration (FDA)‐approved drugs for a new indication may offer an accelerated pathway for new treatments to patients but is also fraught with significant commercial, regulatory, and reimbursement challenges. The Alzheimer's Drug Discovery Foundation (ADDF) and the Michael J. Fox Foundation for Parkinson's Research (MJFF) convened an advisory panel in October 2013 to understand stakeholder perspectives related to repurposing FDA‐approved drugs for neurodegenerative diseases. Here, we present opportunities on how philanthropy, industry, and government can begin to address these challenges, promote policy changes, and develop targeted funding strategies to accelerate the potential of FDA‐approved repurposed drugs.